The Influence of Monetary Economy on The Value of Indonesia's Trade Balance in 2021-2023 - Afiq Ishlahuddin; Muhammad Faza Shafwan; Muhammad Zidane Firdaus; Fitria Rahmah (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Monetary economics plays an important role in maintaining price stability. This study aims to determine the factors in monetary economics that can affect the trade balance in Indonesia in the last 3 years, 2021-2023. The research method uses a quantitative approach with a correlation type of research. The analysis tool is the IBM SPSS program. The data analysis technique is multiple linear regression (Time Series Data). The data source for this research was obtained from the BPS. This study aims to test whether or not there is an influence of monetary economics on the trade balance from the indicator variables X (inflation, interest rates, and exchange rates) to the indicator variable Y (trade balance). Based on the research results, the trade balance is significantly influenced by interest rates, inflation, and exchange rates simultaneously. This shows that monetary and economic factors have an impact on Indonesia's trade balance.